Perancangan Standard Operating Procedures Bisnis Bagi Start Up Air Minum dalam Kemasan Asy-Q - Endah Andayani; Lilik Sri Hariani; Rini Agustina (Jurnal Pemberdayaan Masyarakat, 2022)
Asy-Q mineral water is a business in Islamic boarding schools that produces water to meet the needs of 2900 students spread across 6 Islamic boarding schools and 4 schools within the Asy-Syadzli Pakis Education and Social Foundation Malang. Asy-Q's Mineral Water business has not developed optimally and has not been able to produce to serve the needs of the community outside the pesantren, because it does not yet have a business license. Besides that, there is no standard guide to carry out the management process so this business does not yet have Standard Operating Procedures (SOP) to minimize errors. The community service method uses a participatory approach through coaching and mentoring activities in the preparation of business soups for effective and efficient start-ups. The activity consists of three stages, namely 1) Socialization of the importance of SOP availability; 2) SOP preparation training, and 3) Assistance in formulating effective and efficient SOP strategies that are monitored by business leaders independently and continuously. The results of this community service are to create designs and production SOP guidelines that will be used to support business activities in the form of warehouse SOPs, and distribution SOPs which are the biggest obstacles in business.